A visual analysis of the research literature on teachers’ digital literacy (2015–2024) - Liu, Chong; Xu, Yun (Frontiers in Education, 2025)
This study employs CiteSpace software to conduct a scientific, quantitative, and visual analysis of 169 research articles on teachers’ digital literacy indexed in the Web of Science Core Collection from 2015 to 2024. Aimed at addressing the fragmentation and lack of systematic integration within the field, this analysis reveals the underlying knowledge structure and the evolution of global research, thereby enhancing the theoretical foundation for the digital transformation of education. Utilizing bibliometric methods and visualization techniques, the study identifies interdisciplinary topics such as teacher professional development, digital equity, and STEM education innovation. Highly cited literature emphasizes the construction of conceptual frameworks such as TPACK and the development of assessment tools, while empirical studies predominantly adopt mixed methods to investigate the relationship between technology acceptance and teaching practice. Research frontiers have progressed from basic digital skills training to deeper integration of technology, highlighting the need for competency-based and systematic educational reform. The findings outline key directions for teacher training design, policy coordination, and interdisciplinary collaboration, offering a basis for narrowing the digital divide and reshaping the educational landscape. Furthermore, the results provide empirical support for educational institutions to establish digital literacy standards and enhance strategies for technology integration, thereby advancing both academic discourse and practical efforts in educational digital transformation.